PERETASAN SITUS MILIK DEWAN KEHORMATAN PENYELENGGARA PEMILU OLEH H DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK: Criminal Sanction Aggravation for Hacking of Sites Owned by Indonesian Election Organizer’s Honor Board - Felicia Shadily; Go Lisanawati; Peter Jeremiah Setiawan (Faculty of Law, Maranatha Christian University, 2024)
This article was prepared based on the case of a person with the initials H who hacked a website belonging to the Election Organizer Honorary Council (DKPP). Due to his actions, the court found H guilty of committing a criminal act, without considering the aggravating elements as regulated in the criminal provisions. Based on these issues, the case study in this article aims to examine the application of criminal law penalties for hacking DKPP sites in the criminal provisions of the Law on Electronic Transactions and Information. Based on the normative juridical method and in accordance with the statutory regulatory approach and conceptual approach, H should be proven to fulfill the aggravation element with the addition of one third of the main criminal threat. This was because H hacked intentionally and without the right to change, add, subtract, or hide electronic information belonging to the government, namely the site www.dkpp.go.id. The site belongs to a government agency that has duties and authority regarding violations of the code of ethics by election organizers. The site is also used for various public services related to violations of the code of ethics by election organizers, including complaints and various information services related to DKPP and its duties and authorities.